Diagnosis and Tracking of Past SARS-CoV-2 Infection in a Large Study of Vo', Italy Through T-Cell Receptor Sequencing - Gittelman, Rachel M; Lavezzo, Enrico; Snyder, Thomas M; Zahid, H Jabran; Elyanow, Rebecca; Dalai, Sudeb; Kirsch, Ilan; Baldo, Lance; Manuto, Laura; Franchin, Elisa; Vecchio, Claudia Del; Simeoni, Fabio; et al. (medRxiv, 2020)
In viral diseases T cells exert a prominent role in orchestrating the adaptive immune response and yet a comprehensive assessment of the T-cell repertoire, compared and contrasted with antibody response, after severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection is currently lacking. A prior population-scale study of the municipality of Vo', Italy, conducted after the initial SARS-CoV-2 outbreak uncovered a high frequency of asymptomatic infected individuals and their role in transmission in this town. Two months later, we sampled the same population's T-cell receptor repertoire structure in terms of both diversity (breadth) and frequency (depth) to SARS-CoV-2 antigens to identify associations with both humoral response and protection. For this purpose, we analyzed T-cell receptor and antibody signatures from over 2,200 individuals, including 76 PCR-confirmed SARS-CoV-2 cases (25 asymptomatic, 42 symptomatic, 9 hospitalized). We found that 97.4% (74/76) of PCR confirmed cases had elevated levels of T-cell receptors specific for SARS-CoV-2 antigens. The depth and breadth of the T-cell receptor repertoire were both positively associated with neutralizing antibody titers; helper CD4+ T cells directed towards viral antigens from spike protein were a primary factor in this correlation. Higher clonal depth of the T-cell response to the virus was also significantly associated with more severe disease course. A total of 40 additional suspected infections were identified based on T-cell response from the subjects without confirmatory PCR tests, mostly among those reporting symptoms or having household exposure to a PCR-confirmed infection. Taken together, these results establish that T cells are a sensitive, reliable and persistent measure of past SARS-CoV-2 infection that are differentially activated depending on disease morbidity.
Updated February 11, 2021